P073: Feasibility of emergency department targeted ultrasound for rib fracture diagnosis in minor thoracic injury. (2nd June 2016) - Lalande, E.; Guimont, C.; Émond, M.; Parent, M.; Batomen Kuimi, B.; Boucher, V.; Le Sage, N.
Abstract : Introduction: Rib fractures represent a frequent condition associated with Minor Thoracic Injury (MTI). Since the last decade, ultrasound have become an important part of emergency physician's (EP) daily practice, and its applications have become numerous. The main objective of this study was to evaluate the feasibility of Emergency Department Targeted Ultrasound (EDTU) for rib fracture diagnosis in patients with MTI. Secondary objectives were to 1) evaluate patients' pain during the EDTU procedure, 2) assess clinicians' degree of certitude over rib fracture diagnosis made by EDTU, 3) identify the limitations of the use of EDTU technique, and 4) compare the diagnosis obtained with EDTU to radiography results.Methods: Adult patients who presented with clinical suspicion of rib fractures after MTI were included. All patients underwent EDTU performed by emergency physicians (EP) prior to a rib view X-ray. Visual Analogue Scale (VAS) ranging from 0 to 100 was used to ascertain feasibility, patients' pain and clinicians' degree of certitude. Feasibility was defined as a score of more than 50 on the VAS. We also documented the radiologists' interpretation of rib view X-ray. Radiologists were blinded to the EDTU results.Results: Ninety-six patients were included. A majority (65%) of EP concluded that the EDTU technique to diagnose rib fracture was feasible (VAS score > 50). Median score for feasibility was 63. Median score was 31 (Interquartile range (IQR) 5-57) for patients' pain related to the EDTU examination and 72 (IQR 32-92) for the degree of certitude over the diagnosis made by EDTU. The main limiting factor of the EDTU technique was pain during patient examination (15%).Conclusion: EDTU examination appears to be a feasible technique for rib fractures diagnosis in the ED.